2021
DOI: 10.23917/jmp.v16i1.11413
|View full text |Cite
|
Sign up to set email alerts
|

Konseling Kelompok Menggunakan Teknik Self Control Untuk Mencegah Stres Menghadapi Ujian Nasional

Abstract: Stress is a non-specific body response to any burden over it, stress is a physical reaction to the problems of life experienced. The purpose of this research is the implementation of a group counseling service with self control technique to prevent stress facing national exam-based computer students of Grade XII SMA cooperative Pontianak. This method of research is action research, the form of research is the study of Action guidance and Counseling (PTBK). Data Collector techniques Used (1) direct communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…This has been proven in several previous studies, which revealed that the use of group counseling could decrease students' academic stress (Putrikita & Sari, 2020;Koçak & Çelik, 2022). Group counseling could be done using a range of techniques and approaches to address academic stress, such as self-instruction techniques (Mardianti & Dharmayana, 2020), reality-oriented approaches (Fadhlaturrahmah, 2021), stress inoculation (Sriatun et al, 2023), snake ladderbased group counseling (Novaliany, 2022), self-management techniques (Vania et al, 2019), and self-control techniques (Andriati & Hidayati, 2021), among others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been proven in several previous studies, which revealed that the use of group counseling could decrease students' academic stress (Putrikita & Sari, 2020;Koçak & Çelik, 2022). Group counseling could be done using a range of techniques and approaches to address academic stress, such as self-instruction techniques (Mardianti & Dharmayana, 2020), reality-oriented approaches (Fadhlaturrahmah, 2021), stress inoculation (Sriatun et al, 2023), snake ladderbased group counseling (Novaliany, 2022), self-management techniques (Vania et al, 2019), and self-control techniques (Andriati & Hidayati, 2021), among others.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research shows that the use of group counseling can reduce academic stress levels (Putrikita & Sari, 2020;Koçak & Çelik, 2022). In addition, various techniques and approaches in group counseling have been proven effective in reducing academic stress, including using self-instruction techniques (Mardianti & Dharmayana, 2020), reality approach (Fadhlaturrahmah, 2021), stress inoculation in group counseling (Sriatun et al, 2023), snakes and ladders media in group counseling (Novaliany, 2022), self-management techniques in group counseling (Vania et al, 2019), and self-control techniques in group counseling (Andriati & Hidayati, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Pelaksanaan penerapan konseling kelompok pembayangan terbimbing berfokus solusi (KPPTBS) diharapkan menjadi model pelaksanaan layanan bimbingan dan konseling yang membantu konselor. Model layanan konseling dengan setting kelompok diharapkan menjadi solusi pelaksanaan layanan untuk mencapai keberhasilan layanan bimbingan dan konseling (Andriati & Hidayati, 2021;Himdani, Pramono, & Awalya, 2017).…”
Section: Hasil Dan Pembahasanunclassified